Aggressive digital papillary adenocarcinoma: treatment with Mohs micrographic surgery and an update of the literature. (21st August 2017) - Knackstedt, Rebecca W.; Knackstedt, Thomas J.; Findley, Alyssa B.; Piliang, Melissa; Jellinek, Nathaniel J.; Bernard, Steven L.; Vidimos, Allison
Abstract: Background: Aggressive digital papillary adenocarcinoma (ADPA) is a rare adenocarcinoma of the sweat glands. Aims: We wish to report the treatment of two cases of ADPA with Mohs micrographic surgery and review the presentation, management, and prognosis of this rare malignancy. Materials & Methods: Cases of ADPA were identified from recent surgery logs. Demographic, tumor, and treatment characteristics were extracted. A PubMed database search for English language full‐text articles of aggressive digital papillary adenocarcinoma was performed, and relevant articles were summarized. Results: Two cases of ADPA were identified. A 53‐year‐old man presented with ADPA on his right third fingernail, and a 65‐year‐old man presented with ADPA on his right thumb. Both patients underwent Mohs micrographic surgery and negative sentinel lymph node biopsy, remaining recurrence free at 34 and 9 months, respectively. Discussion: ADPA frequently presents as a solitary mass on the digit. Treatment of ADPA with local excision or amputation has historically been fraught with high recurrence rates. Regional lymph node spread and distant metastasis have been reported. Mohs micrographic surgery may be an alternative treatment for ADPA. Conclusion: Mohs micrographic surgery is a viable option for ADPA and warrants further exploration. Long‐term follow‐up is important, and additional studies will need to identify the role of sentinel lymph node biopsy.